Wpływ ażurowości drzewostanu osłaniającego na wzrost cisa pospolitego (Taxus baccata L.) - Niemczyk, Marzena; Wrzesiński, Piotr; Żółciak, Anna (Leśne Prace Badawcze, 2016)
The aim of this study was to evaluate the development of common yew, Taxus baccata L., with respect to canopy openness. The plants were growing in ex-situ conservation plantations (established in 2008) in the understory of different tree species. Eleven forest plantations belonging to the following five forest districts were inventoried: Rokita, Baligród, Kołaczyce, Międzylesie and Henryków. In each plantation, the height and height increment of 200 yews were measured and gap light transmission indices were determined. The canopy species affecting yew growth most significantly were oak ( Quercus sp.) and Scots pine ( Pinus sylvestris L.), followed by Norway spruce ( Picea abies Karst.), silver fir ( Abies alba L.) and European beech ( Fagus sylvatica L.). The most favorable development of yew occurred at 30% canopy openness. An increasing light transmission index correlated with a decrease in the proportion of treelike yews. An insufficient amount of light resulted in a low height increment of yews growing under the canopy and an extended period of direct competition of yews with herbaceous species.